Developing Sustainable Hajj Funds: Innovative Cash Waqf Investment Models - Fuadi, Nasrul Fahmi Zaki; Farida, Dessy Noor; Saadah, Naili; Ramadhani, Cintya Cindy Melania; Imron, Ali (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
The Indonesian Sharia Economic Masterplan (MEKSI) 2019-2024 presents a detailed plan for the growth of the Islamic financial industry. It focuses on combining the fiscal, commercial, and ZISWAF (Zakat, Infaq, Sadaqah, and Waqf) sectors to promote economic inclusivity. The objective of this study is to assess the management mechanism of the Hajj Fund by BPKH and investigate alternative investment models that make use of cash waqf to enhance the efficiency of fund management. The technique encompasses an extensive examination of existing literature, both qualitative and quantitative evaluations, interviews with relevant stakeholders, and a comparative analysis of successful models implemented in other countries. Financial modeling is utilized to simulate the effects of various asset allocation methods. The results suggest that integrating cash waqf into BPKH's current procedures can lead to considerable improvements. Cash waqf offers higher financial returns and larger social welfare benefits through targeted investments in Sharia-compliant financial instruments such as Sukuk. The iterative process of allocating and reinvesting income guarantees the long-term viability and expansion of Hajj funds. The study highlights the capacity of cash waqf to strengthen financial stability and social influence, in accordance with Islamic principles and promoting economic growth. These findings have significant ramifications for politicians and financial managers in enhancing the management of Hajj funds to more effectively cater to the needs of the Muslim community.